2017
DOI: 10.1123/jtpe.2016-0192
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived and Actual Motor Competency on Children’s Physical Activity and Cardiorespiratory Fitness During Middle Childhood

Abstract: Purpose:Guided by Stodden et al.’s (2008) conceptual model, the purpose of this study was to examine the associations among perceived competence, actual motor competence (MC), physical activity (PA), and cardiorespiratory fitness in elementary children. The group differences were also investigated as a function of MC levels.Methods:A correlational research design was used in this study. There were 262 children (Mage = 10.87, SD = .77) recruited from three schools in the southern U.S. Students’ MC was objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 0 publications
5
27
0
2
Order By: Relevance
“…Further investigation is warranted to test potential mediators between physical literacy and academic reading or math performance. These findings suggest that the instructional environment (i.e., a mastery learning environment; Goodway et al, 2010;Gu et al, 2017) should accommodate for differences across gender and developmental level in building motor competence. Students in our study shared similar PE curricula guided by SHAPE America National Standards, and both genders had equal time/opportunity to practice and learn the motor skills during their PE classes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further investigation is warranted to test potential mediators between physical literacy and academic reading or math performance. These findings suggest that the instructional environment (i.e., a mastery learning environment; Goodway et al, 2010;Gu et al, 2017) should accommodate for differences across gender and developmental level in building motor competence. Students in our study shared similar PE curricula guided by SHAPE America National Standards, and both genders had equal time/opportunity to practice and learn the motor skills during their PE classes.…”
Section: Discussionmentioning
confidence: 93%
“…With respect to gender dynamics, Thomas and French (1985) found that the motor competence disparities between boys and girls widened over the course of development. The extent of childhood or adolescent gender differences in physical literacy is unclear, although it is well documented that girls show a significant decrease in their physical activity and HRF during adolescence (Gu, Thomas, & Chen, 2017;Ortega, Ruiz, Castillo, & Sjostrom, 2008). Some have suggested gender-specific associations in school students between being overweight and showing impairment in certain aspects of developmental functioning, including motor skills, cognitive abilities, and fitness development (Bonvin et al, 2012;Goodway, Robinson, & Crowe, 2010;Krombholz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 22,476 studies were screened based on title and abstract (for a BibTex file, see osf.io/p36rq/). Overall, 93 studies were identified initially that were full-text screened (see Figure 1) but only 19 studies were included in the meta-analysis [13,19,[22][23]26,[33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Of the 74 studies that did not match the eligibility criteria based on full text screening, 45 did not examine the relationship between physical fitness and motor competence, nine did not provide effect sizes or enough information to manually calculate them, and 20 studies operationalized BMI as an aspect of fitness in previous reviews and were therefore excluded.…”
Section: Data Extractionmentioning
confidence: 99%
“…These findings oppose a previous study by Wang et al [31] that analyzed the relationship between PMC and the Control Basketball Dribble Test, which found significant correlations between the two variables. A study done by Gu et al [32] found similar correlations in a younger (e.g., middle childhood) population. The significant correlations between PMC and various MC and HRF measures support the framework created by Stodden and colleagues [9], hypothesizing that the PMC/MC relationships will strengthen over developmental time.…”
Section: Discussionmentioning
confidence: 60%